Study, Investigation and Interpretation (The first four verses of Surat Al-Baqarah) Written by: Al-Fadil Al-Yamani in his Book (Pearl Shells in Al-Kashaf Intricacies’ Solution) - Abdullah, Akram Mohammed (Journal of Islamic Sciences, 2023)
The idea of the research is based on the study and investigation of the first four verses of Surat Al-Baqarah. The primary goal of the study is to clarify complexities and issues in the interpretation of Al-Kashshaf. As for the methodology and nature of the study, it uses the descriptive approach of the personal and scientific life of the author, and the inductive approach by obtaining the manuscript, copying, indicating the author’s sources and reviewing it. This research includes an introduction, two chapters and a conclusion. The first topic is an introductory topic of the author, and the second topic is a model of the investigation. In conclusion, I deduced that Al-Fadil al-Yamani addressed many of the issues raised in his footnotes to Al-Kashaf and provided scientific explanations for some of them, demonstrating the broadness and depth of his knowledge, which is supported by both poetic and Arab language.